Implementasi Metode Pengembangan Multimedia Development Life Cycle (MDLC) Pada Website Pembelajaran Sistem Multimedia - Putri, Dini Ridha Dwiki; Fahlevi, Muhammad Reza; Putri, Fetty Ade (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Learning Media has a very important role in the lecture process which is a guideline for increasing student knowledge in the field of interest. The Multimedia Development Life Cycle (MDLC) Development Method can be used in the development of Learning Multimedia Systems Websites for Multimedia Systems courses. The process of making interactive multimedia applications uses six stages, namely: Concept, Design, Material Collecting, Assembly, Testing, and Distribution. This learning website is equipped with practicum modules and video tutorials that can be downloaded. The making of this learning media uses the programming language PHP, HTML, and CSS on the Sublime Text 3 software and the MySQL database on Xampp. Testing this learning website uses Blackbox Testing to see errors in the assembly process before distribution. This research produces interactive multimedia learning media in the form of a website that can be accessed via the internet (online) which aims to facilitate the learning process for students and even the general public.